Análise dos fluxos no setor de projetos e gerenciamento de obras: estudo de caso em empresa de âmbito nacional - Guimarães, Fábio da Silva (Universidade do Vale do Rio dos Sinos, 2019)
Competitiveness in the construction industry requires companies and organizations to invest more and more in methods and techniques that allow cost reduction and increased profitability. The project is the starting point of the life cycle of a building, in which it is expected that a great part of the decisions will be taken, and solutions found that minimize the environmental impacts, enabling the long-term cost reduction from construction to maintenance and operation of the building. This study aims to analyze and identify the stages of the design process within an architecture and works management office, through a case study where the data collection was done by interviews with structured scripts. Described the process, it was noticed that, although not formalized, there were principles practiced with project stages, like the model used as the basis of the study. Finally, through the results and the bibliography studied it is suggested a flow of steps specific to this case study.
Keywords: Construção civil; Edificações; Projeto; Fluxo de Projeto; Processo de Projeto; Civil construction; Buildings; Project; Project Process; Project Management; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo